INFLUENCE OF VACUUM PACKAGING AND STORAGE TEMPERATURE ON POSTHARVEST SHELF VEST SHELF-LIFE AND QUALITY OF MINIMALLY PROCESSED J Y PROCESSED JACKFRUIT BULBS - R. , GAYATHRI; SATHYANARAYANA, B. N. (The Bioscan, 2016)
The study on influence of vacuum packaging in minimally processed jackfruit bulbs of five different clones were carried out with and without vacuum packaging in polypropylene (300 gauge) and stored in refrigeration (3-50C) and deep freeze (-120 C). There was no detectable total loss in weight (0.18% to 0.45%) in samples under two storage conditions. Vacuum packed samples under deep freeze condition had higher retention of ascorbic acid content of 7.82, 8.37, 8.64, 8.16 and 8.40 mg/100 g for clone1, clone 2, clone 3, clone 4 and clone 5, respectively (ranged from 7.90 to 8.70 mg/100g before packaging) over conventional storage (3-50 C).TSS was found at acceptable levels (ranging from 24.20B to 270B)in samples under deep freeze conditions with vacuum packaging after four weeks of storage over samples under refrigerated conventional packaging (TSS of 26.01 0 B to 280 B) atsecond week of storage itself. The rate of decrease in titrable acidity was slower under deep freeze conditionwith vacuum packaging (0.35% to 0.44%). Higher sensory scores were recorded in vacuum packaged samples under deep freeze as they sustained the quality and fresh-like parameters of jackfruit bulbs. Thus deep freeze storage retarded deteriorative changes and enhanced the shelf-life of jackfruit bulbs.